The development of stretchable and self-repairing materials applied to electronic skin - Li, Mei; Miao, Chuanqi; Zou, Muhua; Guo, Jiahu; Wang, Hongzhen; Gao, Miao; Zhang, Haichang; Deng, Zhifeng (Frontiers in Chemistry, 2023)
Flexible electronic devices play a key role in the fields of flexible batteries, electronic skins, and flexible displays, which have attracted more and more attention in the past few years. Among them, the application areas of electronic skin in new energy, artificial intelligence, and other high-tech applications are increasing. Semiconductors are an indispensable part of electronic skin components. The design of semiconductor structure not only needs to maintain good carrier mobility, but also considers extensibility and self-healing capability, which is always a challenging work. Though flexible electronic devices are important for our daily life, the research on this topic is quite rare in the past few years. In this work, the recently published work regarding to stretchable semiconductors as well as self-healing conductors are reviewed. In addition, the current shortcomings, future challenges as well as an outlook of this technology are discussed. The final goal is to outline a theoretical framework for the design of high-performance flexible electronic devices that can at the same time address their commercialization challenges.